Побудова можливих сценаріїв розвитку процесів як елемент програмування державної політики на довгострокову перспективу (на прикладі житлово-комунальної сфери) - Golyshev, L. K.; Lotocky, O. B.; Vinogradova, V. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
A concept of the state policy in the housing-and-municipal sphere is offered. Necessity to perform numerous application examinations of parameters and forecasts, which demand of known methods for the system analysis (scanning, brain storm, Delfi, Saaty etc.), and also methods of group experts data processing is emphasized.